Steel cathodic protection afforded by zinc, aluminium and zinc/aluminium alloy coatings in the atmosphere - Panossian, Z.; Mariaca, L.; Morcillo, M.; Flores, S.; Rocha, J.; Peña, J.J.; Herrera, F.; Corvo, F.; Sánchez, M.; Rincon, O.T.; Pridybailo, G.; Simancas, J. (Elsevier, 2005)
Zinc has traditionally been the metallic material most widely used to protect steel against atmospheric corrosion due to its ability to afford cathodic protection to steel in all types of natural atmospheres. In recent decades, aluminium and zinc/aluminium alloy coatings have been used instead of zinc in certain atmospheric applications. Although these coatings present some advantages over zinc, they are not able to cathodically protect steel substrates in all types of natural atmospheres. The present paper assesses the cathodic protection afforded by Al (flame spraying), Al/13 Si (hot dipping), 55Al/Zn (hot dipping), Zn/15Al (flame spraying), Zn/5Al (hot dipping), Zn (hot dipping), Zn (discontinuous hot dipping) and Zn (electroplating). Aluminium and aluminium-rich alloy coatings (55%Al/Zn) provide cathodic protection to the steel substrate only in atmospheres that are highly contaminated with chloride ions (>100 mg Cl− m−2 day−1) where these coatings become active.
Keywords: Zinc; Aluminium; Materials science; Metallurgy; Cathodic protection; Alloy; Electroplating; Corrosion; 5005 aluminium alloy; Conversion coating; 5052 aluminium alloy; Aluminium alloy; 6111 aluminium alloy; Layer (electronics); Electrochemistry; Composite material; Electrode; Chemistry; https://purl.org/pe-repo/ocde/ford#2.03.00